Comparison of CD3 and CD8 immunoscoring with histological grade of the tumor in urothelial carcinoma of bladder - Sneha M; Radhika Krishna OH; Sri Lakshmi Gollapalli; Vani Padmaja GJ (Asian Journal of Medical Sciences, 2023)
Background: Inflammatory response within transitional cell carcinoma (TCC) bladder is known to be predictive of tumor prognosis. Lower scores are associated with worser outcome and vice versa. Simpler and cost-effective methods of immunoscoring using immunohistochemistry (IHC) have been described. This study uses two easily available T-cell markers CD3 and CD8 and compares their immunoscore with tumor grade and understands the association. Aims and Objectives: The aims of this study were as follows: (1) To perform immunoscoring for cytotoxic T lymphocytes -CD3+ and CD8+ lymphocytes in urothelial carcinoma and (2) to correlate the immunoscore with tumor grade and calculate its significance in predicting prognosis. Materials and Methods: A prospective cross-sectional study of 2 years duration from October 2018 to October 2020 was conducted at a tertiary level super specialty government institution. All the transurethral resection of bladder tissue biopsies reported as urothelial malignancies during the study period were included in the research. The tumors were graded histologically into high grade and low grade on histology based on the World Health Organization 2016 classification of Urothelial Carcinomas/International Society of Urological Pathology grading system. They were then subject to IHC with two T-cell markers CD3 and CD8 and immunoscoring was done using the method described by Galon. Results: A total of 42 cases of urothelial malignancies were diagnosed during the study period. Cases with higher tumor grade were 25 and lower tumor grade were 17. The association between the lower immunoscore and higher tumor grade was statistically significant. Conclusion: Immunoscoring is a useful adjunct to the routine histological evaluation of TCC. Easily available T-cell markers can be used as simple easy and cost-effective method for immunoscoring.